أثر المُناخ على راحة الإنسان وصحّته في محافظة الخليل-فلسطين - الدعاجنة, حجازي محمد أحمد (Scientific Journal of University of Benghazi, 2021)
This study aimed to detect the impact of climate on humans in two ways:The first side is natural comfort and the second is physical health, The first part deals with the concept of natural comfort and the factors affecting its determination, As for the second aspect of physical health, it deals with the physiological characteristics of the human body and its importance in helping the body to resist climate extremes, The prevailing climate determines the places where endemic diseases are endemic, While local weather patterns determine when these diseases can occur even though people adapt to the conditions in which they live, Human physiology adapts to the climate, There are limits to that ability to adapt, Therefore, these changes are one of the natural causes of human disease because of their differences quarterly.